2017
DOI: 10.56278/tnl.v11i2.531
|View full text |Cite
|
Sign up to set email alerts
|

Number Theory Worktext for Teacher Education Program

Abstract: The lack of available reference materials for Number Theory course intended for the Filipino learners of the Teacher Education Institutions (TEIs) delimits the attainment of the program objectives in terms of content standards. This descriptive-developmental study evaluated and tested the effectiveness of the developed Number Theory Worktext for Mathematics students of Teacher Education programs. The purposively chosen Mathematics professors/instructors, graduate and undergraduate Mathematics major students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These materials can guide learners (Lipscomb et al, 2004), and teachers can transfer knowledge to students spontaneously (Koko, 2016). Many studies claimed that it is imperative to utilize instructional materials to substantiate learning (Awolaju, 2016;Choppin et al, 2022), and teachers have an essential role in providing relevant and appropriate learning sources (Dio, 2017) to promote knowledge acquisition. Similarly, educational materials are undoubtedly vital for the delivery of instruction successfully (Esu et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…These materials can guide learners (Lipscomb et al, 2004), and teachers can transfer knowledge to students spontaneously (Koko, 2016). Many studies claimed that it is imperative to utilize instructional materials to substantiate learning (Awolaju, 2016;Choppin et al, 2022), and teachers have an essential role in providing relevant and appropriate learning sources (Dio, 2017) to promote knowledge acquisition. Similarly, educational materials are undoubtedly vital for the delivery of instruction successfully (Esu et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers might consider students' culture and background in using instructional materials as teaching aids to utilize the same effectively. In addition, selecting appropriate educational material with consideration of learners' mental capability might influence their achievement and rate of performance (Dio, 2017). Moreover, whether it is local or foreign-made, it helps in teaching-learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on instructional materials in the Philippines has also been conducted. These research focused on the creation of educational materials in science and technology (Barquilla & Cabili, 2021;Bibon, 2020;Bigcas et al, 2022;Cruz & Rivera, 2022;Oronce & Manalo, 2021;Rogayan & Dollete, 2019;Soltura, 2022;Urbano, 2020;Variacion et al, 2021), material development in mathematics and engineering (Dio, 2017;Madrazo & Dio, 2020;Mamolo, 2019;Subia, 2020;Terano, 2015;Torrefranca, 2017), baseline studies for instructional development in science (Gregorio et al, 2019), development of digital learning modules in health education (Tolentino et al, 2020), and evaluation of De-pEd-produced modules in biology (Tan, 2019). The literature review found a scarcity of research on the evaluation of science teachers in K12 learner's materials used in public schools.…”
Section: Introductionmentioning
confidence: 99%